Co-infection with bovine herpesvirus type 1 and bovine leukemia virus in dairy cattle in Cajamarca, Peru: A seroprevalence study - Bazán Arce, José Luis (2026)
Bovine herpesvirus type 1 (BoHV-1) and bovine leukemia virus (BLV) are among the most important pathogens affecting dairy cattle, causing significant economic losses worldwide. The present study determined the seroprevalence of IBR (Infectious Bovine Rhinotracheitis) and BLV in dairy herds in Cajamarca, Peru. A total of 464 animals were sampled, and the presence of antibodies against BoHV1 and BLV was determined using commercial indirect enzyme-linked immunosorbent assay (I-ELISA) kits. Among the sampled animals, the overall seroprevalence was 8.84% (95% CI: 0.5–35.12) for BoHV1 and 7.54% (95% CI: 5.13–9.95) for BLV. The highest BLV seroprevalence was observed in Cajamarca (23.68%), while no positive cases were detected in four provinces. Regarding BoHV1 seroprevalence, it was highest in Cajamarca (26.32%) and Santa Cruz (28.13%), with no cases detected in five of the ten provinces evaluated. This indicates that seroprevalence rates varied among the different provinces studied.. Furthermore, 3.66% (95% CI: 1.95-5.38) of the animals tested positive for both BoHV1 and BLV, indicating that they were infected with both viruses simultaneously. The study found that BoHV1 and BLV infections are widespread in numerous provinces of the Cajamarca region, making it necessary to undertake control programmes to prevent the further spread of those two viruses in bovine